2017
DOI: 10.1515/jtim-2017-0030
|View full text |Cite
|
Sign up to set email alerts
|

Bronchial wash Gene Xpert MTB/RIF in lower lung field tuberculosis: Sensitive, superior, and rapid in comparison with conventional diagnostic techniques

Abstract: Background: Lower lung field tuberculosis (LLF TB) is an atypical presentation of tuberculosis (TB). LLF TB is common, and a proportionate number of non-resolving pneumonia cases are diagnosed to have pulmonary TB. Materials and Methods: The prospective observational study was conducted during June 2013 to December 2015 in the Department of Pulmonary Medicine, MIMSR Medical College, Latur, India; the objective of the study is clinical, microbiological, and radiological presentation of LLF TB and the comparison… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
3

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 29 publications
1
13
0
3
Order By: Relevance
“…Similar results were demonstrated by different researchers, such as Lyer VN et al, Mohan A et al and Shin JA et al reporting detection of TB in 30-48% in smear negative patients 16-18. Different studies validated the practical and clinical importance of bronchoscopy in PTB diagnosis 10,15,16,18,19. In all these studies bronchoscopies and BW showed increased detection of TB.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Similar results were demonstrated by different researchers, such as Lyer VN et al, Mohan A et al and Shin JA et al reporting detection of TB in 30-48% in smear negative patients 16-18. Different studies validated the practical and clinical importance of bronchoscopy in PTB diagnosis 10,15,16,18,19. In all these studies bronchoscopies and BW showed increased detection of TB.…”
Section: Discussionsupporting
confidence: 83%
“…Many sputum smear negative patients are reported to have progressive disease 13,14. Previous reports in non-immune compromised patients with sputum sputum-scarce TB indicated that bronchoscope specimens and post bronchoscope sputum are helpful in establishing the diagnosis 9,15. Superiority of Gene Xpert in immunocompromised patients to detect TB as compared to microscopy is debatable.…”
Section: Discussionmentioning
confidence: 99%
“…En el cálculo de la concordancia de resultados de la prueba GeneXpert MTB/RIF frente a cultivo Löwenstein Jensen respecto al azar con el Índice Kappa de Cohen (K)= 0,88, mostró una concordancia clasificada como muy buena (casi perfecto), similar al estudio en Chile (K)= 0,96 13 . La prueba de GeneXpert tiene una sensibilidad de 98 % (IC 95 %), similar a las observadas en Pakistán (78/85) (92 %) 14 , India (155/170) (91 %) 6 , Corea del Sur (35/43) (81,6 %) 15 , Chile (31/33) (94 %) 16 y Sudáfrica (25/27) (93 %) 17 y una especificidad del 96 % (IC 95 %), muy parecida a la encontrada por Lee (97/97) (100 %) 15 , Vallejo (334/351) (95 %) 16 y Theron (127/133) (96 %) 17 .…”
Section: Discussionunclassified
“…La prueba semicuantitativa GeneXpert MTB/RIF de diagnóstico in vitro que detecta componentes del genoma del Mycobacterium tuberculosis (MTB) y resistencia a rifampicina (RIF) se realiza de forma automatizada, purificando y amplificando ácidos nucleicos, identificando la secuencia diana a través de ensayos de reacción en cadena de la polimerasa (PCR) y de PCR con transcriptasa inversa (RT-PCR), ambas en tiempo real. Esta prueba contiene cebadores que amplifican una porción del gen rpoB y sondas que distinguen la secuencia mutada asociada a la resistencia a rifampicina con resultados en dos horas [4][5][6] .…”
Section: Introductionunclassified
See 1 more Smart Citation